Maternal antenatal mood and child development: an exploratory study of treatment effects on child outcomes up to 5 years. (10th October 2018) - Milgrom, J.; Holt, C. J.; Bleker, L. S.; Holt, C.; Ross, J.; Ericksen, J.; Glover, V.; O'Donnell, K. J.; de Rooij, S. R.; Gemmill, A. W.
Abstract: Effective treatment of maternal antenatal depression may ameliorate adverse neurodevelopmental outcomes in offspring. We performed two follow-up rounds of children at age 2 and age 5 whose mothers had received either specialized cognitive-behavioural therapy or routine care for depression while pregnant. Of the original cohort of 54 women, renewed consent was given by 28 women for 2-year follow-up and by 24 women for 5-year follow-up. Child assessments at the 2-year follow-up included the Parenting Stress Index (PSI), Bayley Scales of Infant Development (BSID-III) and the Child Behaviour Checklist (CBCL). The 5-year follow-up included the Wechsler Preschool and Primary Scales of Intelligence (WPPSI-III) and again the CBCL. Treatment during pregnancy showed significant benefits for children's development at age 2, but not at age 5. At 2 years, intervention effects were found with lower scores on the PSI Total score, Parent Domain and Child domain ( d =1.44, 1.47, 0.96 respectively). A non-significant trend favoured the intervention group on most subscales of the CBCL and the BSID-III (most notably motor development: d =0.52). In contrast, at 5-year follow-up, no intervention effects were found. Also, irrespective of treatment allocation, higher depression or anxiety during pregnancy was associated with higher CBCL and lower WPPSI-III scores at 5 years. This is one of the first controlled studies to evaluate the long-term effect of antenatal depression treatment on infant neurodevelopmental outcomes, showing some benefit. Nevertheless, caution should be taken interpreting the results because of a small sample size, and larger studies are warranted.